2018
DOI: 10.1111/1467-9477.12118
|View full text |Cite
|
Sign up to set email alerts
|

A Participatory Personality? Examining the Influence of Personality Traits on Political Participation

Abstract: The aim of this article is to examine whether core personality traits are associated with opinions on and engagement in political participation of either participatory or deliberative nature. The Finish National Election Survey 2015 is used to explore the link between the Big Five personality dimensions and a wide array of political opinions and behaviour. The results suggest that variations in personality to some extent affect what kind of activities one prefers and engages in. Personality traits seem to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…As political participation is at the heart of democracy, understanding what makes people engage in politics is a key issue for political scientists and communication scholars alike (Verba, Schlozman, and Brady, 1995). In the related literature, there is an ongoing scholarly debate on the role of personality traits as determinants of political and prosocial behavior (Cooper, Golden, and Socha, 2013;Bloeser et al, 2015;Dinesen, Nørgaard, and Klemmensen, 2014;Jennstål, Uba, and Öberg, 2020;Kline et al, 2019;Lindell and Strandberg, 2018;Margetts et al, 2015;Rasmussen and Hebbelstrup, 2016). These effects have been studied at different geographic contexts, including the Netherlands (Bekkers, 2005), Finland (Mattila et al, 2011), Venezuela and Uruguay (Mondak et al, 2011), South Korea (Ha, Kim, and Jo, 2013), India and Pakistan (Oskarsson and Widmalm, 2016), Italy (Caprara et al, 2006), and Germany (Schoen and Steinbrecher, 2013).…”
mentioning
confidence: 99%
“…As political participation is at the heart of democracy, understanding what makes people engage in politics is a key issue for political scientists and communication scholars alike (Verba, Schlozman, and Brady, 1995). In the related literature, there is an ongoing scholarly debate on the role of personality traits as determinants of political and prosocial behavior (Cooper, Golden, and Socha, 2013;Bloeser et al, 2015;Dinesen, Nørgaard, and Klemmensen, 2014;Jennstål, Uba, and Öberg, 2020;Kline et al, 2019;Lindell and Strandberg, 2018;Margetts et al, 2015;Rasmussen and Hebbelstrup, 2016). These effects have been studied at different geographic contexts, including the Netherlands (Bekkers, 2005), Finland (Mattila et al, 2011), Venezuela and Uruguay (Mondak et al, 2011), South Korea (Ha, Kim, and Jo, 2013), India and Pakistan (Oskarsson and Widmalm, 2016), Italy (Caprara et al, 2006), and Germany (Schoen and Steinbrecher, 2013).…”
mentioning
confidence: 99%
“…There may be another reason that members of ČSSD (a left-wing party) were higher in extraversion. Politicians were found to be higher than the population in extraversion in Italy (Caprara et al, 2003) and politically active people were found higher in extraversion in Finland (Lindell & Strandberg, 2018). ČSSD was a party that had been in power for seven years in 2005 and the delegates who were elected to represent the strongest party in a regional summit were probably close to professional politicians.…”
Section: Discussionmentioning
confidence: 96%
“…Political interest is a consistent predictor of online (Lindell and Strandberg 2018) and offline discussion (Grill 2019;Lindell and Strandberg 2018). Lindell and Strandberg (2018) found that age matters for online discussion, but not offline discussion; gender does not predict either mode of discussion. Other studies find that gender predicts political discussion (Grill 2019;Song and Boomgaarden 2019) and like-minded discussion (Mondak 2010;Mondak et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Extraverts are more sociable and assertive, which increases the propensity to talk politics (Grill 2019;Hibbing et al 2011;Lindell and Strandberg 2018). They may prefer political discussion as a form of political participation because it is a sociable and interactive activity, as opposed to individualized activities such as signing petitions (Evans and Ulbig 2012;Lindell and Strandberg 2018). Extraverted people are also more likely to have larger social networks and a greater number of interactions within these networks (Hibbing et al 2011;Mondak 2010).…”
Section: Personality and Political Talkmentioning
confidence: 99%